Climate Change and Microbial Ecology Current Research and Future Trends. - Marxsen, Jürgen (Caister Academic Press, 2020)
In the first edition of this acclaimed book, a broad range of renowned scientists reviewed the most important hot-topics in the area of climate change and microbial ecology, thus providing a timely and authoritative overview of this increasingly important area. Climate change is continuing unabated and this new, expanded edition contains revised and updated chapters and the addition of four new chapters covering more of the topical fields in this important area of climate science. This is an essential book for every microbial ecologist from the PhD student to the experienced scientist and is a.